Penegakan Hukum terhadap Tindak Pidana Penipuan Melalui Media Sosial dan Perlindungan Terhadap Korbannya di Wilayah Daerah Istimewa Yogyakarta - Taufik Langgeng Ardiansyah; Ari Wibowo (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research discusses law enforcement against criminal acts of fraud via social media in the Yogyakarta Special Region. This type of research is empirical legal research with a sociological approach. Data sources consist of primary data in the form of interviews and secondary data in the form of primary, secondary and tertiary legal materials. Data collection methods include interviews and literature study. The results of this research are, first, law enforcement against criminal acts of fraud via social media in the Yogyakarta Special Region, namely with preemptive efforts, preventive efforts and repressive efforts. In enforcing the law, the Yogyakarta Regional Police experienced obstacles, and data requests took a long time. Second, legal protection for victims of criminal acts of fraud via social media in the Special Region of Yogyakarta has two aspects, namely procedural and substantive. In the investigation process, victims' procedural rights must be fulfilled in the form of the right to be served fairly, the right to obtain information regarding the legal process, the right to be accompanied by a legal advisor, the right to provide information and evidence, and the right to receive protection and security.